2015
DOI: 10.1002/app.42677
|View full text |Cite
|
Sign up to set email alerts
|

Melt blending of polylactide and poly(methyl methacrylate): Thermal and mechanical properties and phase morphology characterization

Abstract: Blends of polylactide with poly(methyl methacrylate), PLA/PMMA, were prepared by a semi-industrial twin screw extruder and afterwards were injection molded. Blends were studied using different techniques as Fourier Transform Infrared Spectroscopy (FTIR), Dynamic Mechanical Analysis (DMA), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), and mechanical properties by means of tensile and impact tests, were also studied. This work helped better understanding of apparently contradictory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 31 publications
(39 reference statements)
9
51
0
Order By: Relevance
“…The appearance of a single T g is evidence for miscibility over the entire composition range. A broad range for the T g is observed for blends with 25 wt % and 50 wt % PLA both with and without glass fiber which is consistent with the findings of previous investigations . Importantly, crystalline melting peaks are also observed for the 25 wt %, 75 wt %, and 100 wt % PLA systems without glass fiber and for the 75 wt % and 100 wt % PLA samples when fibers are present.…”
Section: Resultssupporting
confidence: 90%
“…The appearance of a single T g is evidence for miscibility over the entire composition range. A broad range for the T g is observed for blends with 25 wt % and 50 wt % PLA both with and without glass fiber which is consistent with the findings of previous investigations . Importantly, crystalline melting peaks are also observed for the 25 wt %, 75 wt %, and 100 wt % PLA systems without glass fiber and for the 75 wt % and 100 wt % PLA samples when fibers are present.…”
Section: Resultssupporting
confidence: 90%
“…Anakabe et al [44] studied the effect of melt blending PLA and poly(methylmethacrylate) to find a single Tg for the blends after heating them to 250°C in a DSC apparatus, with a value intermediate to those for individual polymers and impact toughness similar to the neat polymer in which they were rich. The authors also noted the effect of processing temperature on the final Tg of the blend since they discovered that the blends processed at 215°C depicted dual Tg transitions due to polymer immiscibility below the UCST of 230°C [37].…”
Section: Thermal and Mechanical Propertiesmentioning
confidence: 98%
“…However, these blends are immiscible and, in an immiscible blend, the glass-transition temperature of PLA remains unchanged. 20,21 In a previous study on the properties and phase structure of PLA/PMMA blends, it was revealed that a sufficiently long melt blending period is crucial to obtain a single-phase material. Very few polymers are miscible with PLA.…”
Section: Introductionmentioning
confidence: 99%